Prolonged Use of Oritavancin for Vancomycin-Resistant Enterococcus faecium Prosthetic Valve Endocarditis. (29th October 2015) - Johnson, Jennifer A.; Feeney, Eoin R.; Kubiak, David W.; Corey, G. Ralph
Abstract: Oritavancin is a novel lipoglycopeptide with activity against Gram-positive organisms including streptococci, methicillin-resistant Staphylococcus aureus, vancomycin-resistant S aureus (VRSA), and vancomycin-resistant enterococci (VRE) [1–3 ]. The US Food and Drug Administration approved oritavancin as a single intravenous dose of 1200 mg for the treatment of acute bacterial skin and skin structure infections on the basis of 2 clinical trials demonstrating noninferiority compared with vancomycin [4, 5 ]. There are limited options for treatment of serious VRE infections. Monotherapy with daptomycin or tigecycline or linezolid may be sufficient in some cases, but combination therapy is often indicated for severe or complicated infections such as endocarditis. Several antibiotic combinations have been used in isolated case reports with some efficacy, including the following: high-dose ampicillin with an aminoglycoside [6 ], ampicillin with ceftriaxone or imipenem [7, 8 ], high-dose daptomycin with ampicillin and gentamicin [9 ] or with gentamicin and rifampin [10 ], daptomycin with tigecycline [11, 12 ], quinupristin-dalfopristin with high-dose ampicillin [13 ] or doxycycline and rifampin [14 ], and linezolid with tigecycline [15 ]. The limited efficacy, limited susceptibility, and extensive toxicities with many of these agents and combinations present barriers to effective treatment. Additional treatment options for VRE endocarditis would be valuable. Although oritavancin has been shown to have in vitro activity against some isolates of VRE, clinical data are lacking. We describe the first use of a prolonged course of oritavancin in the treatment of a serious VRE infection, prosthetic valve endocarditis.